Obstacles and opportunities for sustainable consumption: A comprehensive conceptual model, literature review, and research agenda - Andrade, Eduardo B.; Vieites, Yan (Journal of Consumer Psychology, 2025)
Abstract Meaningful shifts in consumption habits are essential to mitigate climate change and reduce global environmental degradation. Yet, despite the climate urgency and growing consumer concerns, the widespread adoption of sustainable behaviors has proven difficult. Why is this the case? How has the growing interdisciplinary field of sustainable consumption contributed to this debate? And where are the knowledge gaps? Guided by a comprehensive conceptual model, this article (a) delves into the key market , individual , and s ocietal obstacles that hinder consumers from adopting more environmentally sustainable behaviors, (b) explores how practitioners and policymakers can help consumers minimize or circumvent these deterrents, and (c) highlights the pressing gaps in the literature, offering a roadmap for advancing our understanding of how to promote sustainable practices across the consumer journey—from search and purchase to usage and disposal.